Passive Control of Base Pressure: A Review - Ambareen Khan; Parvathy Rajendran; Junior Sarjit Singh Sidhu (Applied Sciences, 2021)
In the present world, passive control finds application in various areas like flow over blunt projectiles, missiles, supersonic parallel diffusers (for cruise correction), the engine of jets, static testbeds of rockets, the ports of internal combustion engines, vernier rockets, and single expansion ramp nozzle (SERN) rockets. In this review, various passive control techniques to control the base pressure and regulate the drag force are discussed. In the study, papers ranging from subsonic, sonic, and supersonic flow are discussed. Different types of passive control management techniques like cavity, ribs, dimple, static cylinder, spikes, etc., are discussed in this review article. This study found that the passive control device can control the base pressure, resulting in an enhancement in the base pressure and reducing the base drag. Also, passive control is very efficient whenever there is a favorable pressure gradient at the nozzle exit.